2015
DOI: 10.1080/21645515.2015.1087627
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between autoimmunity and specific immunotherapy for allergic diseases

Abstract: The aim of this study was to perform a 20-year post-specific immunotherapy (SIT) observational evaluation for an assessment of any manifestations of autoimmune disease or the appearance of autoantibodies in serum. In total, 1,888 patients (902 women and 986 men) were observed. The mean age of the patients was 34.1 §12.4 y at the start of the prospective observation after finishing SIT. New incidences of autoimmune disease and/or the presence of autoantibodies in serum were monitored. The SIT group was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…The presence of autoantibodies in serum reflects leakiness of central and/or peripheral tolerance and may lead to the manifestation of autoimmune diseases [ 24 ]. A plethora of evidence has suggested that serum autoantibodies participate in the progress of allergic diseases [ 55 , 56 ]. We confirmed that a higher incidence of AR patients presented with autoantibodies in blood samples, with histones as the prevalent antigen, which is congruent with previous studies in animal models [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of autoantibodies in serum reflects leakiness of central and/or peripheral tolerance and may lead to the manifestation of autoimmune diseases [ 24 ]. A plethora of evidence has suggested that serum autoantibodies participate in the progress of allergic diseases [ 55 , 56 ]. We confirmed that a higher incidence of AR patients presented with autoantibodies in blood samples, with histones as the prevalent antigen, which is congruent with previous studies in animal models [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allergen can cause autoimmune disease such as scleroderma, arthritis and rhinitis [40,41]. Immunotherapy is used to treat AR, and immunotherapy of AR affects B-cell differentiation and decreases B-cell sensibility [42].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy can be applied to treat cancer, autoimmune diseases, and allergic diseases by activating or regulating these immune cells depending on the condition of the disease. 48,49 Recently, immune checkpoint blockade and CAR T-cell therapy have been approved by the FDA as promising cancer therapy methods. Since CRISPR can precisely edit the target genes of immune cells, its application could further extend the potential of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%